Multiple scalp metastases from pulmonary adenocarcinoma seen on fluorodeoxyglucose positron-emission tomography/computed tomography - Doudouh, Abderrahim; Oueriagli, Salah Nabih; Sahel, Omar Ait; Benameur, Yassir (World Journal of Nuclear Medicine, 2020)
Scalp metastasis from a primary visceral malignancy is an uncommon clinical entity. Here, we report a case of scalp metastases from lung cancer seen on fluorodeoxyglucose positron-emission tomography-computed tomography.
Keywords: Fluorodeoxyglucose positron-emission tomography/computed tomography; lung cancer; scalp neoplasm